2011
DOI: 10.1111/j.1600-0447.2010.01581.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose–response relationship of sertindole and haloperidol using the pharmacopsychometric triangle

Abstract: This re-analysis confirmed the antipsychotic effect and absence of extrapyramidal effects for sertindole and, in addition, showed a clinically significant antidepressant effect. A profile for bipolar states emerged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…As in our previous study [8], the pharmacopsychometric triangle was found to have a high degree of communicative validity. The effect size statistics when comparing active T-PEMF with sham T-PEMF clearly indicated the superiority of the active T-PEMF in terms of antidepressive effect and the patients' self-reported quality of life.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…As in our previous study [8], the pharmacopsychometric triangle was found to have a high degree of communicative validity. The effect size statistics when comparing active T-PEMF with sham T-PEMF clearly indicated the superiority of the active T-PEMF in terms of antidepressive effect and the patients' self-reported quality of life.…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, the pharmacopsychometric triangle has been introduced to give an overall clinical outcome profile of an intervention [7, 8], taking into account the wanted antidepressive effect, the unwanted side effects, and the patients' own balanced evaluation of health-related quality of life. The pharmacopsychometric triangle is scientifically connected to effect size statistics [9, 10], as it allows us to evaluate diverse outcome scales (wanted versus unwanted effect as well as subjective quality of life) by reference to an integrated unit, namely, the standard deviation of the improvement scores [7].…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacopsychometric triangle (2,3) provides an integrated overview of the available study information in three essential domains: desired effects, undesirable effects, and quality of life. The pharmacopsychometric triangle (2,3) provides an integrated overview of the available study information in three essential domains: desired effects, undesirable effects, and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…In our analysis to be reported here, we have focussed on the pharmacopsychometric triangle to better evaluate the overall treatment outcome of this measurement based care study in the acute treatment of outpatients with major depression. The pharmacopsychometric triangle (2,3) provides an integrated overview of the available study information in three essential domains: desired effects, undesirable effects, and quality of life. This illustrative triangle, recently used for analysis of another large study (3), is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation